1992
DOI: 10.7164/antibiotics.45.38
|View full text |Cite
|
Sign up to set email alerts
|

Cinatrins, a novel family of phospholipase A2 inhibitors. I. Taxonomy and fermentation of the producing culture; isolation and structures of cinatrins.

Abstract: Cinatrins A, B, Cl5 C2 and C3, a family of phospholipase A2 inhibitors were isolated from the fermentation broth of Circinotrichum falcatisporum RF-641. They were found to be novel spiro-y-dilactones and y-lactones derived from 1 ,2,3,5-tetra or 1 ,2,3(or l ,2,4)-trihydroxypentadecane-1,2,3-tricarboxylic acids. Structures were elucidated by MSand NMRstudies and chemical transformations. The structure of cinatrin C3 was confirmed by X-ray crystallographic analysis, and its absolute configuration was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 18 publications
3
36
0
1
Order By: Relevance
“…Therefore, ascotricins A and B are novel antagonists of S1P 1 . We also found that aranorosin, 22 analogs of caloporoside 23 and cinatrins 24,25 had S1P 1 antagonist activity (data not shown). All of these, including ascotricins, are amphipathic compounds and are also thought to be analogs of Sph-1-P. Ascotricins inhibited HUVEC migration, and this indicates that ascotricins and their related S1P 1 antagonists might have antiangiogenic activity.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, ascotricins A and B are novel antagonists of S1P 1 . We also found that aranorosin, 22 analogs of caloporoside 23 and cinatrins 24,25 had S1P 1 antagonist activity (data not shown). All of these, including ascotricins, are amphipathic compounds and are also thought to be analogs of Sph-1-P. Ascotricins inhibited HUVEC migration, and this indicates that ascotricins and their related S1P 1 antagonists might have antiangiogenic activity.…”
Section: Discussionmentioning
confidence: 70%
“…Coelomycetes is typically found in leaf litter. However, most of Coelomycetes was not sporulated while culturing in the laboratory (Itazaki et al, 1992). Number of those moulds can only be identified based on morphology reproduction structure in their host.…”
Section: Resultsmentioning
confidence: 99%
“…Found: 297.1366. (m,2H,Ar). δ C (CDCl 3 , 75 MHz) 11.35, 25.93, 41.18, 64.45, 79.68, 109.22, 112.80, 127.56, 131.85, 132.72, 140.32, 180.81 11.21,41.16,64.30,79.98,109.31,113.40,127.35,132.50,132.81,140.00,190.79.…”
Section: -(2-benzylaminophenyl)-3-hydroxy-4-methyldihydrofuran-2-one 14mentioning
confidence: 98%
“…R F 0.5 (50:50 hexane/EtOAc). ν max /cm −1 (CH 2 Cl 2 ) 3405 (OH, NH), 2941, 1781, 1718, 1600. δ H (CDCl 3 , 300.1 MHz) 0.61 (d, J 6.9, 3H, CH 3 ), 1.94 (br s, 2H, OH and NH), 2.5 (m, 1H), 3.92 (dd, J 11.1 and 4.5, 1H), 4.18 (dd, J 11.1 and 9.6, 1H), 4.75 (d, J 15.6, 1H), 4.98 (d, J 15.6, 1H), 6.57 (d, J 8.1, 1H, Ar), 7.28-7.48(m, 7H, Ar). δ C (CDCl 3 , 75 MHz)11.59, 41.11, 64.65, 79.64, 104.78, 116.21, 122.11, 123.44, 127.01, 127.21 (2C), 127.89 (3C), 130.01, 132.39, 141.82, 196.58.…”
mentioning
confidence: 99%